Penerapan Model Pembelajaran Scaffolding Terhadap Kemampuan Pemahaman Konsep Matematis di Kelas VII SMP Negeri 5 Semparuk - Riya, Riya; Haryadi, Rahman; Abdillah, Abdillah (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to find out the ability to understand mathematical concepts after applying the scaffolding learning model and ordinary learning and to find out in school VII SMP Negeri 5 Semparuk. The research method used in this study is quantitative with a type of quasi-experiment (quasi-experiment). The sample was selected using the cluster random sampling technique. The instrument in this study is in the form of questions about the ability to understand mathematical concepts. The data analysis used is quantitative descriptive. The results of the analysis showed that the ability to understand mathematical concepts in grade VII of SMP Negeri 5 Semparuk which applied the scaffolding learning model obtained an average of 72.21. The ability to understand mathematical concepts in grade VII of SMP Negeri 5 Semparuk which applied the usual learning model obtained an average of 39.85. The ability of students to understand mathematical concepts taught with the scaffolding learning model is better than that taught with the usual learning model in grade VII of SMP Negeri 5 Semparuk.